Evaluasi Alih Fungsi Lahan Pertanian Terhadap Pendapatan Petani Di Kecamatan Bacukiki Kota Parepare - Lukman, Lukman (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
The shift in land use in the City of Parepare, in general, has undergone quite a drastic change, with some areas of agricultural land having been converted into built-up areas. The direction of the development of the City of Parepare as an industry for health services, education, tourism, as well as a transit area attracts people from outside the region to invest in land, buildings or to live in this area. The population density and limited land in urban areas make development towards suburban areas, especially Bacukiki District. Based on this, research was conducted to examine the factors that influence the conversion of agricultural land and the impact of the conversion of agricultural land on the economic condition of farmers. The research is located in Bacukiki District, Parepare City, with a quantitative descriptive method. The data obtained in this study was carried out by direct observation and interview techniques using a questionnaire of 30 respondents who had converted paddy fields. The Bivariate analysis results showed no significant difference between farmers' income before and after land conversion; in other words, land conversion had no significant effect on farmers' income